2016
DOI: 10.1111/myc.12457
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance to fluconazole induced by exposure to the agricultural azole tetraconazole: an environmental resistance school?

Abstract: This study aimed to investigate the influence of tetraconazole and malathion, both used in agricultural activities, on resistance to fluconazole, itraconazole and voriconazole in Candida parapsilosis ATCC 22019. The susceptibility to tetraconazole, malathion, fluconazole, itraconazole and voriconazole, through broth microdilution. Then, 12 independent replicates, were separated and exposed to four treatment groups, each one containing three replicates: G1: tetraconazole; G2: malathion; G3: fluconazole (positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
(104 reference statements)
0
25
0
Order By: Relevance
“…By 2005, Denmark already used 100 tonnes of azole fungicides, nearly the same amount as Norway used of total fungicides in 2011 (http://www2.mst.dk). The agricultural azole tetraconazole was recently demonstrated to induce fluconazole cross resistance in C. parapsilosis in vitro when exposed to increasing concentrations over a 7 week period . It has also been reported that azole‐resistant Candida isolates have been found in lake water and in a porcupine in Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…By 2005, Denmark already used 100 tonnes of azole fungicides, nearly the same amount as Norway used of total fungicides in 2011 (http://www2.mst.dk). The agricultural azole tetraconazole was recently demonstrated to induce fluconazole cross resistance in C. parapsilosis in vitro when exposed to increasing concentrations over a 7 week period . It has also been reported that azole‐resistant Candida isolates have been found in lake water and in a porcupine in Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…albicans , emphasising the contribution of these pumps for the development of azole resistance. Moreover, this variability in RFU values is expected between isolates of the same species and even between clones of the same isolate, as demonstrated by Rocha et al., who reported that replicates of the same azole‐resistant isolate showed variable fluorescence values that were compatible with enhanced efflux activity. Even though no significant correlations between efflux activity and gene expression were found in this study, Bhattacharya et al.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, we hypothesise that strains from veterinary sources may acquire azole resistance after exposure to environmental stressors . Even though non‐human Candida strains are not commonly submitted to selective pressures by azoles of clinical use, this pressure still occurs through the environmental exposure to this class of antifungals, especially in agricultural practices, and cross‐resistance between these drugs and those azoles used in medical and veterinary practice has been detected . Chowdhary et al., for instance reported the occurrence of azole‐resistant Aspergillus fumigatus infections in treatment‐naive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations